الخطُّ العربيُّ من الأساطيرِ الغَيْبِيَّةِ إلى الجُهُودِ البَشَرِيَّة - الأستاذ الدكتور مصطفى محمد رزق السواحلي (Journal of Calligraphy, 2022)
No doubt, that Allah has chosen Arabic calligraphy to write the words of the Holy Qur’an, and gave it magnificence and beauty that was not available to any other calligraphy. So it with its exquisite geometric shapes paints some unlimited beautiful images, even it became an independent art. Arabs were satisfied with it for obscene images and nude statues, and this geometric formation became an aesthetic feature that gave Islamic civilization a special character throughout the ages. This transcendent beauty led a group of scholars to say that it descended from the divine in this wonderful image that is beyond the human capacity, and Arabic heritage books have been loaded with dozens of narrations in this field .This is what this research attempts to achieve, in order to differentiate between what is the metaphysical that needs a definitive text of proof and significance, and what is the human as a product of the cumulative efforts of the experiences of scientists and creators throughout the ages, which requires a rational, moderate position on the issue of the unseen generally, then to present a number of those narrations scattered in the wombs of the books of Arab heritage, and criticize them as a narration and knowledge. Then to mention those who borrowed Arabic calligraphy from the neighboring nations before Islam, and who developed it after Islam, until it became an Islamic industry par excellence, through the descriptive analytical method. In the end the research concluded with a number of results, the most important of them are: Belief in the unseen is a religious duty, provided that there is a valid evidence from the authentic revelation, which is lacking in the narrations that are filled inside the books of Arab heritage that attribute the development of Arabic calligraphy to a group of those who passed away, starting with Adam, peace be upon him. Some scholars have escaped from confronting this problem to the saying of revelation, which has no evidence for it, if it was by inspiration; there was no difference or development in it, as it did not happen in the Holy Qur’an. Most realistic narrations indicate that the Arabs borrowed their calligraphy from the neighboring nations, especially from the Nabataean script in the Anbar region. The bond between the writing and civilization is an inseparable bond, which is what was achieved for Arabs after the appearance of Islam, which makes us to say: It is an Islamic industry par excellence, and the follow-up of the efforts of Arab scholars in the field of developing Arabic calligraphy confirms that the calligraphy is a human industry, developed by the scholars who spent their ages in serving the sciences and arts in Arabic language.